Response of Endophytic Microbial Communities and Quality of Salvia miltiorrhiza to Fertilization Treatments - Wenjing Chen; Wanyun Li; Yangyang Pan; Xin Zheng; Xinxin Fu; Menghui Wang; Wenyi Shi; Zhenzhou Wang; Xueli He; Chao He; Xianen Li (Microorganisms)
Salvia miltiorrhiza is a traditional herbal remedy for cardiovascular diseases and is in high demand in the market. Excessive chemical fertilizer application, resulting from unscientific fertilization practices, reduced the tanshinone content in S. miltiorrhiza roots. This study investigated how different fertilization types alter the endophytic microbial community composition of S. miltiorrhiza through field experiments, aiming to understand how fertilization affects its medicinal quality. The results showed that root fertilizers (F1) significantly increased root biomass and tanshinone I content, whereas foliar fertilizers (F2) increased tanshinone IIA content. High-throughput sequencing further revealed that F2 treatment significantly decreased the Shannon index of endophytic bacteria while significantly increasing the Shannon index of endophytic fungi. Co-occurrence network analysis revealed that fertilization significantly altered fungal community complexity and modularity, with F1 increasing network nodes and edges. Variance partitioning analysis indicated fungal diversity more strongly influenced medicinal compound levels under F2 and a combination of both (F3) than bacterial diversity. Septoria and Gibberella were positively correlated with tanshinone I and cryptotanshinone content under F2 treatment, respectively. Notably, the unique strains were isolated from different fertilization treatments for subsequent bacterial fertilizer development. These findings elucidate microbial responses to fertilization, guiding optimized cultivation for improved S. miltiorrhiza quality.